‘Breast Cancer Resistance Likelihood and Personalized Treatment Through Integrated Multiomics’ - Mehmood, Sabba; Faheem, Muhammad; Ismail, Hammad; Farhat, Syeda Mehpara; Ali, Mahwish; Younis, Sidra; Asghar, Muhammad Nadeem (Frontiers in Molecular Biosciences, 2022)
The researchers have made enormous progress in improving the diagnosis and therapeutic strategies for breast carcinoma. But it still remains the most prevalent cancer and second highest contributor in cancer-related deaths in women. Breast cancer affects one in eight females globally. In 2018, 1.4 million cases were identified worldwide in postmenopausal women and 645000 cases in premenopausal females and this burden is continuously rising. This shows that still a lot remains to be discovered regarding the treatment options. One of the major clinical complications in the treatment of breast carcinoma patients is the development of therapeutic resistance. Multidrug resistance (MDR) and consequent relapse on therapy is a prevalent issue related to breast carcinoma as our understanding is incomplete related to molecular mechanism of breast carcinoma disease. Therefore, elucidating the molecular mechanisms involved in drug resistance is critical. For management of the breast carcinoma, the treatment decision not only depends on the assessment of prognosis factors but also on the evaluation of pathological and clinical factors. Integrated data assessments of these multiple factors of breast carcinoma through multiomics can provide significant insight and hope for making therapeutic decision. This omics approach is particularly helpful since it identifies biomarkers of disease progression and treatment progress by collective characterization and quantification of pools of biological molecules within and among the cancerous cells. The scrupulous understanding of cancer and its treatment at molecular level led to the concept of personalized approach, which is one of the most significant advancements in modern oncology. Likewise, there are certain genetic and non-genetic tests available for breast cancer (BC) which can help in personalized therapy. Genetically inherited risks can be screened for personal predisposition to breast cancer, as well as genetic changes or variation (mutations) can also be identified to decide on the best treatment. Ultimately, with further understanding of breast cancer at the molecular level (multiomics) will define more precise choices in personalized medicine.